Autoimmune polyglandular syndrome type I: a case report - Cinaz, Peyami; Bideci, Aysun; Haznedaroğlu, Ahmet; Ezgü, Fatih Süheyl; Ağaoğlu, Ömür; Kürşaklıoğlu, Sevilay (The Turkish Journal of Pediatrics, 1997)
Autoimmune polyglandular syndrome (APS) type I is a disorder that consists of three primary diseases: hypoparathyroidism (HPT), adrenocortical insufficiency (ACI) and chronic mucocutaneous candidiasis. Several other disorders may be associated. The diagnosis of APS type I was made in a 16-year-old patient with HPT, Hashimato’s thyroiditis and ACI in our department. She has been observed for more than four years for other possible endocrine and non-endocrine disorders.